Postnatal Hematopoiesis and Gut Microbiota in NOD Mice Deviate from C57BL/6 Mice - Dina Silke Malling Damlund; Stine Broeng Metzdorff; Jane Preuss Hasselby; Maria Wiese; Mia Lundsager; Dennis Sandris Nielsen; Karsten Stig Buschard; Axel Kornerup Hansen; Hanne Frøkiær (Journal of Diabetes Research)
Neonatal studies in different mouse strains reveal that early life colonization affects the development of adaptive immunity in mice. The nonobese diabetic (NOD) mouse spontaneously develops autoimmune diabetes, but neonatal studies of NOD mice are lacking. We hypothesized that NOD mice deviate from another much used mouse strain, C57BL/6, with respect to postnatal microbiota and/or hematopoiesis and compared this in newborn mice of dams housed under the same conditions. A distinct bacteria profile rich in staphylococci was found at postnatal days (PND) 1–4 in NOD mice. Furthermore, a distinct splenic cell profile high in a granulocytic phenotype was evident in the neonatal NOD mice whereas neonatal C57BL/6 mice showed a profile rich in monocytes. Neonatal expression of Reg3g and Muc2 in the gut was deviating in NOD mice and coincided with fewer bacteria attaching to the Mucosal surface in NOD compared to C57BL/6 mice.